Work Step by Step
The x-intercept of the equation $x - y = 3$ can be found by substituting in $0$ for $y$ ($y$ will be zero at the equation's x-intercept). Thus: $x - 0 = 3$ $x = 3$ at the equation's x-intercept. Therefore, the equation passes through the point $(3, 0)$. At the equation's y-intercept, $x = 0$. Thus: $0 - y = 3$ $y = -3$ at the equation's y-intercept, and the equation passes through the point $(0, -3)$. If we plot these two points and draw the line that passes through them, we will get the graph of this linear equation.